A fully integrated chaos generator based on voltage controlled oscillator. (August 2022) - Duan, Zhikui; Wang, Huwei; He, Shaobo; Li, Shiren; Yan, Shiquan; Zhao, Xiaomeng; Yu, Xinmei; Yang, Guangguang; Tan, Haishu
Abstract: A new integrated chaos generator based on Voltage-Controlled-Oscillators (VCO) is proposed in this paper. The proposed generator consists of a nonlinear resistor and RC coupling circuit integrated with VCO. It is fully integrated instead of using discrete components compared with the traditional chaotic circuits. The proposed circuit exhibits excellent performances in the stable power supply, low power consumption, and small chip area cost. This chaotic circuit is fabricated in SMIC 180 nm CMOS process and it occupies a chip area of 0.039 mm 2 . The simulation results show that the proposed circuit could work in the frequency range from 11 MHz to 36 MHz with the maximum 2.0892 mW power consumption with a 1.8 V power supply. The range of the Lyapunov exponent is from 0.5628 to 2.2136. It shows potential application values of the designed fully integrated chaotic circuit.